2011
DOI: 10.1007/s00425-011-1513-x
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex-related changes in cytokinins, auxins and abscisic acid in a centenarian relict herbaceous perennial

Abstract: It is still an unsolved question of fundamental biology if, and how, perennial plants senesce. Here, age- and sex-related changes in phytohormones were tested in Borderea pyrenaica, a small dioecious geophyte relict of the Tertiary with one of the longest lifespan ever recorded for any non-clonal herb (more than 300 years). Biomass allocation, together with levels of cytokinins, auxins and absicisic acid, and other indicators of leaf physiology (chlorophylls, lipid peroxidation and F (v)/F (m) ratio) were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
(71 reference statements)
0
8
0
1
Order By: Relevance
“…These studies concluded that females seem to be more sensitive to environmental stress and usually experience greater negative effects. In other cases, female plants exhibited better tolerance of adverse conditions than males, females showed a more conservative strategy of water use or higher photosynthetic rates compared with males 4, 3335 . For example, Male and female P. angustifolia genotypes grew similarly with favorable water levels, but males tended to be more inhibited by flooding, while females were more flood tolerant 4 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies concluded that females seem to be more sensitive to environmental stress and usually experience greater negative effects. In other cases, female plants exhibited better tolerance of adverse conditions than males, females showed a more conservative strategy of water use or higher photosynthetic rates compared with males 4, 3335 . For example, Male and female P. angustifolia genotypes grew similarly with favorable water levels, but males tended to be more inhibited by flooding, while females were more flood tolerant 4 .…”
Section: Discussionmentioning
confidence: 97%
“…For example, Male and female P. angustifolia genotypes grew similarly with favorable water levels, but males tended to be more inhibited by flooding, while females were more flood tolerant 4 . Females of some perennial herbs are more resistant to drought stress than males 35 . Therefore, the information available thus far is insufficient for establishing generalizations about whether male and female dioecious plants show differential abiotic stress resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism can lead to profound differences in secondary sexual characters, such as vegetative growth and plant response to both biotic and abiotic stresses; but the extent to which these stresses can affect photoinhibition, photoprotection, and photo-oxidative stress in dimorphic plants is still very poorly understood. Previous studies have shown that females are generally more sensitive to photoinhibition that males when subjected to either drought stress ( Li et al, 2004 , 2007 ; Xu et al, 2008a , b ; Rozas et al, 2009 ; Chen et al, 2010 , 2014 ; Zhang et al, 2010 , 2014 ; Kumar et al, 2016 ) or low temperatures ( Li et al, 2007 ; Zhang et al, 2011 ; Juvany et al, 2014 ), although some exceptions exist (e.g., see Oñate et al, 2012 ; Morales et al, 2013 ; He et al, 2016 ). In the present study, it was found that females are more sensitive than males to photoinhibition only during the summer.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in phytohormone contents during leaf senescence in perennial plants are generally in agreement with their function in annual plants. For example, in the perennial herb Borderea pyrenaica , ABA content increased during leaf senescence, whereas the contents of cytokinins and auxin decreased ( Oñate et al , 2012 ). In mastic trees ( Pistacia lentiscus ) the content of the cytokinin zeatin was reduced in older compared with younger plants and negatively correlated with the chlorophyll a / b ratio ( Juvany et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%